Orality made writing in El libro de las ciudades by Celso Román - Numpaque Acosta, Andrea María; Alarcón Cepeda, Milena; Numpaque Acosta, Galo Christian (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The objective of this article is to present evidences of how the literature and orality advance together along the same path, accompanied in writing by the elements it contains, such as fantasy, memory, and tradition. From the orality made in writing in dialogues that suggests the reading of the work of CelsoRomán El libro de lasciudades, and that in turns allows understand that there is a transmission from the oral to writing inspired by the city. In this way,Roman’s writing proposes an approach to the traditional orality that reflects craft, artistic and peasant activities that are seen in the city, addingfan  tasy to his narration promoting in this way the popular tradition